Synthesis of Methyl Lactate from Glucose over Alkali-Modified Sn-H-Y Catalysts - Majidov, Ramin; Aho, Atte; Vajglova, Zuzana; Kumar, Narendra; Lassfolk, Robert; Angervo, Ilari; Tirri, Teija; Lastusaari, Mika; Eränen, Kari; Mäki-Arvela, Päivi; Hietala, Jukka; Murzin, Dmitry Yu. (SPRINGER, 2025)
Glucose transformation to methyl lactate was investigated over microporous Sn-H-Y- zeolite with SiO2/Al2O3 ratio of 30 as well as alkali metal modified mesoporous dealuminated Sn-H-Y-zeolites in the temperature range of 150-180oC. The catalysts were synthesized either by evaporation-impregnation or ion-exchange methods using a two-step procedure for Sn-and K-modification. The catalysts were characterized by several physico-chemical methods including SEM, TEM, pyridine adsorption-desorption FTIR, UV-VIS spectroscopy, solid state NMR-spectroscopy, nitrogen adsorption, TGA and CHNS for spent catalysts. The highest yield of methyl lactate of 72% was obtained at 150oC over dealuminated K-Sn-H-Y-30 catalyst at complete glucose conversion. Especially low K/Sn ratio was preferential for maximizing methyl lactate yield. Catalyst regeneration and leaching were also investigated.